Federal institutes of education: a new paradigm in professional and technical education? - Vicente Zatti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The present article analyze the technological and professional education proposal of the Federal Institutes of Education on deployment in Brazil since 2008. Founded theoretically in Jurgen Habermas philosophy and Paulo Freire pedagogy, from the analysis of the pertinent legislation and the targeted interviews, we search answer if the proposal mentioned represents a new paradigm in professional and technological education. We identify the emancipation concept as the central of the discussion for the fact of some proposal report in your discussions a emancipation pretension. Some proposal characteristics as a dichotomy between technical capacitation and human formation, the proposition of the integrated curriculum, the uprighting, the training for a creativity, appointed to a overcoming of one technicist historical that configure a new paradigm in technological and professional education.